Insights into Cu2O thin film absorber via pulsed laser deposition. Issue 11 (1st June 2022) - Kartha, Chithira Venugopalan; Rehspringer, Jean-Luc; Muller, Dominique; Roques, Stéphane; Bartringer, Jérémy; Ferblantier, Gérald; Slaoui, Abdelilah; Fix, Thomas
Abstract: Cuprous oxide materials are of growing interest for optoelectronic devices and were produced by several chemical and physical methods. Here, we report on the structural, optical, and electrical properties of Cux O thin films prepared by the pulsed laser deposition technique. The substrate temperature, as well as the oxygen partial pressure in the deposition chamber, were varied to monitor the copper to oxygen ratio within the deposited films. The growth conditions were carefully optimized to provide the highest conductivity and mobility. Thus, 100 nm thick cuprous oxide films (Cu2 O) deposited at 750 °C exhibited a resistivity of 16 Ω∙cm, high mobility of 30 cm 2 /(V∙s), and a bandgap of around 2 eV. The film deposited at the optimized deposition parameters on Nb:STO (001) substrate with Au top electrode showed a photovoltaic response with an open circuit voltage of 0.56 V. These results path the way to efficient solar cells made with Cu2 O films via the pulsed laser deposition technique. Graphical abstract: Image 1